2014
DOI: 10.1074/jbc.m114.559328
|View full text |Cite
|
Sign up to set email alerts
|

YES, a Src Family Kinase, Is a Proximal Glucose-specific Activator of Cell Division Cycle Control Protein 42 (Cdc42) in Pancreatic Islet β Cells

Abstract: Background: Although Cdc42 signaling is a known requirement for insulin secretion to occur, how it is initiated remains unknown. Results: YES kinase is required for Cdc42 activation in human islets and ␤ cells. Conclusion: YES is a proximal, glucose-specific activator of Cdc42 and glucose-simulated insulin secretion. Significance: YES may provide a novel target for improvement of functional ␤ cell mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 73 publications
5
30
0
Order By: Relevance
“…However, in smooth muscle cells SFK activation was not needed for the angiotensin II-mediated activation of PAK[85]. These findings that activation of SFKs is frequently upstream of PAKs activation are consistent with studies demonstrating SFKs are important in the activation of the PAK activators, Rac and CDC42, by a number of stimulants[103,106,107]. These results reveal that the GI hormone/neurotransmitter, CCK, demonstrates a number of unique features related to its receptor activation-state in activating signaling cascades to stimulate PAK2 activation.…”
Section: Discussionsupporting
confidence: 69%
“…However, in smooth muscle cells SFK activation was not needed for the angiotensin II-mediated activation of PAK[85]. These findings that activation of SFKs is frequently upstream of PAKs activation are consistent with studies demonstrating SFKs are important in the activation of the PAK activators, Rac and CDC42, by a number of stimulants[103,106,107]. These results reveal that the GI hormone/neurotransmitter, CCK, demonstrates a number of unique features related to its receptor activation-state in activating signaling cascades to stimulate PAK2 activation.…”
Section: Discussionsupporting
confidence: 69%
“…12c). Previous study also showed that tyrosine kinase Yes, the closest member of Src among the Src family kinases (SFKs), is activated by glucose36. Consistently, add-back glucose induced Yes phosphorylation, but not Src and Fyn (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, recent investigations by Yoder et al [28] provide compelling evidence for YES tyrosine kinase activation as an early signalling event (~1 min) involved in the activation of the small G protein Cdc42 (~3 min) in glucose-stimulated islet beta cell. Likewise, studies of Garrett et al have demonstrated a requirement for tyrosine phosphorylation of VAV2 in vascular endothelial growth factor-induced Rac1 activation in endothelial cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several Src family tyrosine kinases (SFKs) such as Lck and Fyn [23, 24], Syk family tyrosine kinases (Syk and Zap70) [24, 25], and receptor tyrosine kinases [26, 27] have been implicated as mediators of VAV2 tyrosine phosphorylation. Recent studies have shown that activation of tyrosine-protein kinase Yes (an Src family kinase) is indispensable for Cdc42 activation in a glucose-specific manner in pancreatic beta cells [28]. The aim of the current study, therefore, was to understand the roles of VAV2 in islet function, including GSIS.…”
Section: Introductionmentioning
confidence: 99%